From 'celluloid comrades' to 'digital video activism': queer filmmaking in postsocialist China - Bao, Hongwei (Cardiff University Press, 2018)
Although homosexuality was decriminalised in 1997 and partially depathologised in 2001, LGBTQ issues are still strictly censored in Chinese media. With the rapid growth of China’s LGBTQ community, an increasing number of independent films featuring LGBTQ issues have emerged in the past two decades. In this article, I trace a brief history of queer cinema in the People’s Republic of China in the postsocialist era (1978 to present). In particular, I chart the significant turn from ‘celluloid comrades’, i.e. queer people being represented by heterosexual identified filmmakers in an ambiguous way, to what leading Chinese queer filmmaker Cui Zi’en calls ‘digital video activism’, in which LGBTQ identified individuals and groups have picked up cameras and made films about their own lives. In doing so, I unravel the politics of representation, the dynamics of mediated queer politics and the political potential of queer filmmaking in China. I suggest that in a country where public expressions of sexualities and demands for sexual rights are not possible, queer filmmaking has become an important form of queer activism that constantly negotiates with government censorship and the market force of commercialisation. Rather than representing a pre-existing identity and community, queer films and filmmaking practices have brought Chinese gay identities and communities into existence.